PENERAPAN PROSEDUR HIGIENE PEMERAHAN UNTUK MENGINGKATKAN KUALITAS SUSU SEBAGAI IMPLEMENTASI GOOD DAIRY FARMING PRACTISE - Merryafinola ifani; Afduha Nurus Syamsi; Yusuf Subagyo; Hermawan Setyo Widodo (Fakultas Ekonomi & Bisnis Universitas Jenderal Soedirman, 2024)
The Andhini Lestari and Andhini Rahayu Livestock Groups are groups of smallholder breeders whose maintenance is still carried out conventionally. Poor milking sanitation and hygiene management is still a problem for this group of farms. Farmers conventionally carry out milking with a very low level of hygiene. Milking hygiene needs to be considered because it will affect udder health. Udder health affects the quality and quantity of milk produced. Unhealthy milking hygiene will cause the udder to suffer from mastitis which is very detrimental to the farmer. So, to maintain good milk quality, farmers must follow milking hygiene procedures as an implementation of Good Dairy Farming Practices. A series of activities that will be carried out are training in making disinfectant solutions and dipping teas, making milking SOPs, applying Good Dairy Farming Practices. The aim of carrying out this PKM is to form cadres of breeders in the Andhini Lestari and Andhini Rahayu groups, Karangtengah Village, Cilongok District, Banyumas and breeders in the surrounding areas; Maintaining good milk quality at the smallholder level through implementing good milking hygiene; And prevents the occurrence of mastitis in dairy cows.